2015
DOI: 10.2319/011715-37.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of shear bond strength and bonding time of a novel flash-free bonding system

Abstract: Objective: To evaluate the bonding time, shear bond strength (SBS), and adhesive residue index (ARI) of APC(TM) Flash-Free bonding system. Materials and Methods: Thirty-six extracted human maxillary premolars were randomly divided into three groups (12 per group) and used for this in vitro study: group 1, APC Flash-Free Adhesive Coated Appliance System; group 2, Clarity ADVANCED Ceramic Bracket pasted manually; group 3 (control group), 3M APC PLUS Adhesive prepasted brackets bonded with the extruded flash remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 12 publications
5
36
3
5
Order By: Relevance
“…In vitro studies of this bracket system have demonstrated adequate bond strength, 8,11 reduced bonding time, 11,12 and microleakage 8 comparable to traditional bonding systems. Grunheid et al 8 calculated the volume of silver nitrate microleakage under the Flash-Free system using microcomputed tomography, but they did not stress their samples prior to evaluation.…”
Section: Introductionmentioning
confidence: 91%
“…In vitro studies of this bracket system have demonstrated adequate bond strength, 8,11 reduced bonding time, 11,12 and microleakage 8 comparable to traditional bonding systems. Grunheid et al 8 calculated the volume of silver nitrate microleakage under the Flash-Free system using microcomputed tomography, but they did not stress their samples prior to evaluation.…”
Section: Introductionmentioning
confidence: 91%
“…Adhesive-precoated brackets have been used widely in clinical orthodontics [9] as the tooth-bonding time is short [10]. Recently, systems precoated with "flash-free" adhesives have become available.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Thus, 3M Unitek has developed a novel adhesive coated appliance system (APC Flashfree) to minimize flash amounts, to improve the bond strength and reducing the microleakage. [15][16][17] It is composed of a low viscosity resin applied to a non-woven polypropylene mesh that attached to the orthodontic bracket base. 17 The bond strength of flash-free adhesive to CAD/CAM provisional material has not been investigated previously.…”
Section: Introductionmentioning
confidence: 99%